(untitled) (Diametros, 2009)
The goal of an ethics case discussion is to find the best decision for the patient and the other persons involved (relatives, doctors, nurses and others) from an ethical point of view, in a communicative respect and from a psychosocial view. In the end, it may not mean changing one’s view or even one’s own position, but rather to exchange arguments, weight them and come to a consensus as to further action. The latter is important as the topics concern patients and require action. For the moderator an ethics case discussion in this sense is no judgement, no taking over of responsibility for the decision result, no taking over of a leading role, and no team supervision. However, ethics case discussion has become a valuable tool to deal with moral conflicts in hospitals. Opportunities and problems of ethics case discussions are discussed. A 4-step approach for structuring the course of an ethics case discussion is presented.